Designing an Industrial Policy for Developing Countries: A New Approach - Ali Haeri; Abbas Arabmazar (ZBW – Leibniz Information Centre for Economics, 2019)
In this study, the prevalent methodology for design of the industrial policy in developing countries was critically assessed, and it was shown that the mechanism and content of classical method is fundamentally contradictory to the goals and components of the endogenous growth theories. This study, by proposing a new approach, along settling Schumpeter's economic growth theory as a policy framework, designed the process of entering, analyzing and processing data as the mechanism of the industrial policy in order to provide "theoretical consistency" and "technical and Statistical requirements" for targeting the growth stimulant factor effectively. – – در این مقاله با استدلال منطقی و علمی ضرورت دو رویکرد "تعمیق آماری و فنی" و "تعمیق تئوریک" برای تدوین و اجرای یک خط مشی صنعتی مورد تاکید قرار گرفت.در این راستا، به سبب بیشترین تطابق تئوری رشد اقتصادی شومپیتر با آنچه که اساسا هدف یک خط مشی صنعتی برای یافتن عامل محرک درونزای سیستم اقتصادی و تقویت و کانالیزه کردن آن در مسیر رشد اقتصادی است، و همچنین با چرخش از متد کلاسیک به سوی متد جدیدی که داده های ورودی به مکانیزم تدوین و اجرای خط مشی صنعتی «طرح تولید محصول» باشد، بستر لازم برای اجرایی شدن این دو رویکرد فراهم شد.
Keywords: O00; O20; O25; O38; E61; L52; 330; industrial policy; Schumpeter; endogenous economic growth; new combinations; technology; stimulant factor